INSILICO ANALYSIS OF STRUCTURAL IMPACT OF N171A IN ENDO-Β-N ACETYLGLUCOSAMINIDASES - SHECHINAH FELICE.CHORAGUDI,; B V RAMAN,; BONDILI J S, (International Journal of Pharma and Bio Sciences, 2015)
Endo-β-N-acetylglucosaminidases (ENGases) are important enzymes having dual specificity with an ability to catalyze hydrolysis and transglycosylation reactions. Because of their potential for synthesis of glycopeptides, these enzymes have become the focus of intense research. In this study, Energy minimization and subsequent Molecular dynamic simulations were performed for 10ns timescale to understand the stability and conformational differences among ENGase orthologs using Desmond. We compared ENGase orthologous proteins of bacteria, plant and Humans. Since, there is no crystal structure of Plant and Human available, we used homology modeled structures [OPR] and for bacteria Artherobacterial ENGase (PDB 3FHQ) were used. The results obtained from RMSF Graphs clearly indicates that, when compared to bacterial ENGase, the plant and Human ENGases showed high flexibility all along protein structures. Further, there was a clear deviation in flexibility at catalytic domains of bacteria where as in the other two eukaryotes, the deviation in the flexibility was in the gate keeper domain and transglycosylation sites where amino acid tryptophan and phenylalanine were replaced with Aspargine and tyrosine respectively. This change is found to be naturally evolved and should be attributing higher transglycosylation rates in human and plants.